Menarche's Experience In Adolescents Scoping Review - Nahdiyatul Mukaromah; Ismarwati Ismarwati (International Journal of Health Science and Technology, 2021)
Menarche is a sign of physical maturity and fertility. The preparation has an impact on the menarche experience in adolescents. Menarche is seen as a transitional period associated with religious and socio-cultural significance. The purpose of this review is to describe the menarche experience in adolescents. This review uses arksey O'Malley framework with 5 stages namely: identifying questions, identifying relevant articles, selecting articles, mapping charting data, compiling, summarizing and creating reports. The results of 6 literatures were selected with two themes that appeared, namely positive and negative attitudes and changes that occurred in adolescents with menarche.